Patient Participation in Clinical Ethics Interventions: A Requirement of Procedural and Epistemic Justice - Eijkholt, Marleen (Bioethics, 2026)
The question whether or not patients ought to be involved in clinical ethics interventions (CEI) remains unresolved. While generally it has been recognized that patients’ active participation in health care decisions and processes is important, this is not unequivocally accepted for CEIs. Patient participation in CEI (PP) is common in the United States, but PP seems far from the prevailing practice in Europe. In Europe, CEIs often involve discussions of the ethics issue by the healthcare team only; the patient or proxy is not included, consulted or even informed about such an intervention. In this paper, we submit that policies or standards which resist PP and disable it as an option conflict with procedural and epistemic justice requirements in CEIs. We conceptually develop how the two concepts of procedural justice (PJ) and epistemic justice (EJ) relate to CEIs and to PP. We also engage with four cases to illustrate the risks of injustices and how PP facilitates CEIs to meet justice requirements. We conclude that in settings where CEIs systematically do not involve PP, and where patients are neither asked about the ethics issue nor informed about the intervention, policy and practice presumptions should be adjusted.